Dispersed surface Ru ensembles on MgO(111) for catalytic ammonia decomposition - Fang, Huihuang; Wu, Simson; Ayvali, Tugce; Zheng, Jianwei; Fellowes, Joshua; Ho, Ping-Luen; Leung, Kwan Chee; Large, Alexander; Held, Georg; Kato, Ryuichi; Suenaga, Kazu; Reyes, Yves Ira A.; et al. (Nature communications, 2023)
Ammonia is regarded as an energy vector for hydrogen storage, transport and utilization, which links to usage of renewable energies. However, efficient catalysts for ammonia decomposition and their underlying mechanism yet remain obscure. Here we report that atomically-dispersed Ru atoms on MgO support on its polar (111) facets {denoted as MgO(111)} show the highest rate of ammonia decomposition, as far as we are aware, than all catalysts reported in literature due to the strong metal-support interaction and efficient surface coupling reaction. We have carefully investigated the loading effect of Ru from atomic form to cluster/nanoparticle on MgO(111). Progressive increase of surface Ru concentration, correlated with increase in specific activity per metal site, clearly indicates synergistic metal sites in close proximity, akin to those bimetallic N 2 complexes in solution are required for the stepwise dehydrogenation of ammonia to N 2 /H 2 , as also supported by DFT modelling. Whereas, beyond surface doping, the specific activity drops substantially upon the formation of Ru cluster/nanoparticle, which challenges the classical view of allegorically higher activity of coordinated Ru atoms in cluster form (B 5 sites) than isolated sites. Ruthenium-based materials show promising performance for ammonia decomposition, yet the underlying mechanism remains to be further explored. Here the authors investigate atomically dispersed Ru atoms on polar (111) on MgO facets to show synergistic metal sites in close proximity are required for the stepwise dehydrogenation of ammonia to N2/H2.